Value of volume-based metabolic parameters for predicting survival in breast cancer patients treated with neoadjuvant chemotherapy. Issue 41 (October 2016) - Kim, Tae Hee; Yoon, Joon-Kee; Kang, Doo Kyoung; Kang, Seok Yun; Jung, Yong Sik; Han, Sehwan; Kim, Ji Young; Yim, Hyunee; An, Young-Sil
Abstract : Abstract: We evaluated the role of metabolic parameters in the prediction of disease recurrence in operable invasive ductal breast cancer patients treated with neoadjuvant chemotherapy (NAC). We retrospectively evaluated 139 female patients (mean age, 46.5 years; range: 27–72 years) with invasive ductal breast cancer, treated with NAC followed by surgery. All patients underwent 18 F-fluorodeoxyglucose positron emission tomography/computed tomography and magnetic resonance imaging at baseline and after completion of NAC before surgery. The prognostic significance of clinicopathological and imaging parameters for disease-free survival (DFS) was evaluated. Recurrence of cancer was detected in 31 of 139 patients (22.3%; follow-up period: 6–82 months). Baseline maximum standardized uptake value, metabolic tumor volume (MTV), and reduction rate (RR) of MTV after NAC were significant independent prognostic factors for DFS in a multivariate analysis (all P  < 0.05). The survival functions differed significantly between low and high histological grades ( P  < 0.001). DFS of the patients with high baseline MTV (≥5.23 cm 3 ) was significantly poorer than that of low MTV patients ( P = 0.019). The survival function of the group with low RR of MTV after NAC (≤90.72%) was poorer than the higher RR of the MTV group ( P = 0.008). Our findings suggest that breast cancer patients who have a high histological grade, large baseline MTV, or a small RR of MTV after NAC should receive great attention to check for possible recurrence.